Anti-cutting rock plate and preparation method thereof

By optimizing the raw material formula of the rock slab body layer, a low-eutectic quaternary composite flux is formed, which solves the problem of cutting and cracking of rock slabs during mechanical processing, and achieves fast burning at low temperatures, reducing production energy consumption and firing time, and significantly improving the anti-cutting performance and strength.

CN119859052AActive Publication Date: 2025-04-22FOSHAN DONGPENG CERAMIC +3
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202510352188.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-25
Publication Date
2025-04-22
Estimated Expiration
2045-03-25

AI Technical Summary

Technical Problem

Existing rock slabs are prone to cutting and cracking during machining, and although traditional high-temperature slow burning technology can improve the anti-cutting performance, it increases production energy consumption and firing time.

Method used

By optimizing the raw material formula of the blank layer, including the use of bentonite, magnesium soil, waste brick powder, waxite, sodium feldspar and mixed mud, the eutectic K2O-Na2O-MgO-CaO quaternary composite flux is formed, which promotes the formation of the liquid phase and densification of the blank layer, thereby achieving low temperature and rapid firing.

Benefits of technology

The sintering temperature of the rock slab is reduced to 1223°C and the sintering cycle is shortened to 35-38 minutes, which significantly improves the anti-cutting performance and strength and reduces production energy consumption.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of architectural ceramics, in particular to an anti-cutting rock plate and a preparation method thereof, and the anti-cutting rock plate comprises a green body layer, a ground coat layer, a decorative layer and a glazed layer which are sequentially arranged from bottom to top; the green body layer is prepared from the following raw materials in parts by mass: 1 to 3 parts of bentonite, 3 to 5 parts of magnesia soil, 22 to 28 parts of waste brick powder, 11 to 15 parts of washed mud, 28 to 35 parts of pyrophyllite, 12 to 16 parts of albite and 8 to 12 parts of mixed mud; the chemical components of the waste brick powder, the pyrophyllite, the albite and the mixed mud comprise SiO2, Al2O3, Fe2O3, TiO2, CaO, MgO and K2O; the content of SiO2 in the waste brick powder, the content of pyrophyllite, the content of albite and the content of Al2O3 in the mixed mud are 65%-75% and 13%-20% respectively according to the mass percent; the mixed mud comprises the following mineral components in percentage by mass: 50-60% of kaolinite and 40-50% of free quartz. According to the anti-cutting rock plate provided by the invention, the anti-cutting performance and the strength can be improved on the premise of realizing low-temperature fast firing.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of building ceramics, and in particular to a cutting-resistant rock cracking plate and a preparation method thereof. Background Art

[0002] Rock board is a new type of ceramic material made from natural raw materials through slurry ball mill grinding, drying spray tower granulation process, hydraulic press pressing, and kiln firing. As a new variety in the field of building ceramics, rock board has been popular in the market due to its strong durability, good hardness and strong decorative effect, and is widely used in home and kitchen board fields.

[0003] Before using, the rock slab generally needs to be machined by cutting, grinding, drilling and chamfering. However, since the rock slab is a brittle material, according to incomplete statistics, there is a 10-20% probability of cutting cracks when the rock slab products are machined, which affects the later use of the product. In order to improve this shortcoming, the traditional technology adopts high temperature slow burning (firing temperature exceeds 1260℃, and the firing cycle is 50-70min), aiming to use high temperature slow burning to promote the development and growth of mullite crystals, increase the content of mullite crystals, and use the higher strength and thermal shock resistance of mullite crystals to enhance the anti-cutting cracking performance of the rock slab. However, although the above method has its effect, the dispersion of mullite crystals in the glass phase of the rock slab is usually poor, which can easily lead to local agglomeration and enrichment of mullite crystals, thereby causing stress concentration, which may aggravate the generation of cutting cracks, making the improvement of anti-cutting cracking performance limited. In addition, the above-mentioned high-temperature slow-burning technical means not only increases the calcination temperature, but also prolongs the calcination time, which is not conducive to achieving low-temperature fast burning, reducing production energy consumption and improving corporate competitiveness.

[0004] Since the anti-cutting cracking performance of the rock slab mainly depends on the green body layer, in order to overcome the above defects, the existing technology improves the raw materials of the green body layer, aims to reduce the firing temperature and firing cycle, and achieve low-temperature fast firing, thereby increasing the mullite content formed during the calcination process and the dispersion of mullite crystals, thereby improving the anti-cutting cracking performance of the rock slab. However, due to the selection of raw materials and differences in preparation technology, the produced rock slabs still have technical defects such as high firing temperature, long firing time and poor anti-cutting cracking. Summary of the invention

[0005] The purpose of the present invention is to propose a cutting crack resistant rock plate, which, by improving the raw materials of the green body layer, is beneficial to reducing the firing temperature and firing cycle, and achieving low-temperature fast firing, thereby improving the cutting crack resistance and strength, so as to overcome the shortcomings of the prior art.

[0006] Another object of the present invention is to propose a method for preparing a cutting and cracking resistant rock plate, whose firing temperature is as low as 1223°C and the firing cycle is as low as 35 to 38 minutes. The preparation method is simple and easy to operate, which is beneficial to improving the cutting and cracking resistance and strength while reducing the firing temperature and firing cycle and achieving low-temperature and fast firing, so as to meet actual use needs.

[0007] To achieve this object, the present invention adopts the following technical solutions: A cutting and cracking resistant rock board comprises a body layer, a base glaze layer, a decorative layer and a polishing glaze layer arranged in sequence from bottom to top; Calculated by weight, the raw materials of the green body layer include: 1-3 parts of bentonite, 3-5 parts of magnesia clay, 22-28 parts of waste brick powder, 11-15 parts of washed mud, 28-35 parts of pyrophyllite, 12-16 parts of albite and 8-12 parts of mixed mud; The chemical components of the waste brick powder, the pyrophyllite, the albite and the mixed mud all include SiO2, Al2O3, Fe2O3, TiO2, CaO, MgO and K2O; Calculated by mass percentage, the content of SiO2 in the waste brick powder, the pyrophyllite, the albite and the mixed mud is 65-75%, and the content of Al2O3 is 13-20%; Calculated by mass percentage, the mineral components of the mixed mud include 50-60% kaolinite and 40-50% free quartz.

[0008] Further, calculated by mass percentage, the chemical composition of the waste brick powder includes SiO2 65-66%, Al2O3 18-19%, Fe2O3 1.7-1.8%, TiO2 0.50-1%, CaO 0.5-0.7%, MgO 1.7-1.8%, K2O 1.9-2% and Na2O 2-2.1%, and the rest is loss on ignition; The particle size of the waste brick powder is ≤0.85 mm.

[0009] Furthermore, calculated by mass percentage, the chemical composition of the pyrophyllite includes SiO2 70-73%, Al2O3 18-20%, Fe2O3 0.5-0.8%, TiO2 0.4-0.5%, CaO 0.2-0.3%, MgO 0.1-0.2%, K2O 2.3-2.4% and Na2O 0.1-0.2%, and the rest is loss on ignition.

[0010] Furthermore, calculated by mass percentage, the chemical composition of the albite includes SiO2 68-70%, Al2O3 16-18%, Fe2O3 0.1-0.2%, TiO2 0.05-0.1%, CaO 0.5-0.6%, MgO 0.1-0.2%, K2O 0.6-0.7% and Na2O 8-8.1%, and the rest is loss on ignition.

[0011] Furthermore, calculated by mass percentage, the chemical composition of the mixed mud includes SiO2 70-70.5%, Al2O3 19-20%, Fe2O3 1-1.2%, TiO2 0.3-0.4%, CaO 0.4-0.5%, MgO 0.2-0.3%, K2O 1-1.1% and Na2O 0.2-0.3%, and the rest is loss on ignition.

[0012] Furthermore, calculated by mass percentage, the chemical composition of the washed mud includes SiO2 50-53%, Al2O3 31-33%, Fe2O3 1.4-1.5%, TiO2 0.1-0.2%, CaO 0.1-0.2%, MgO 0.2-0.3%, K2O 3-3.2% and Na2O 0.3-0.4%, and the rest is loss on ignition.

[0013] Furthermore, calculated by mass percentage, the chemical composition of the magnesia soil includes SiO2 62-63%, Al2O3 5.7-5.8%, Fe2O3 1.6-1.7%, TiO2 0.1-0.2%, CaO 0.7-0.8%, MgO 19.5-20%, K2O 0.2-0.3% and Na2O 0.2-0.3%, and the rest is loss on ignition.

[0014] A method for preparing a cutting-resistant rock cracking plate, for preparing the cutting-resistant rock cracking plate, comprises the following steps: A. After mixing the formulated amount of bentonite, magnesia clay, waste brick powder, washed mud, pyrophyllite, albite and mixed mud evenly, adding water to ball mill and sieving to obtain slurry; spray granulating the slurry to obtain a blank; pressing the blank into shape, and drying to obtain a blank layer; wherein the fineness of the ball mill is a 325 mesh sieve, and the sieve residue is 1.3-1.8% calculated by mass percentage; B. Applying base glaze on the surface of the body layer to obtain a base glaze layer; C. Printing color ink on the surface of the base glaze layer according to a preset pattern to obtain a decorative layer; D. Apply glaze on the surface of the decorative layer to obtain a glaze layer; E. After drying, the material is put into a kiln for firing to obtain a cutting-resistant rock board; wherein the firing temperature of the cutting-resistant rock board is ≤1223°C, and the firing cycle is 35 to 38 minutes.

[0015] Furthermore, in step A, the specific method of screening is: filtering the raw material of the green body layer after water ball milling through a 40-mesh sieve, a 60-mesh sieve, and an 80-mesh sieve in sequence, and then filtering twice through a 110-mesh sieve.

[0016] Furthermore, in step E, the firing curve of the anti-cutting and cracking rock plate includes a preheating section, a first pre-temperature section, a strong oxidation section, a second pre-temperature section, a medium temperature section, a high temperature section, a transition section, a rapid cooling section and a slow cooling section; The top temperature of the preheating section rises from room temperature to 854°C, and the bottom temperature rises from room temperature to 841°C, which takes 5 to 5.4 minutes; The top temperature of the first pre-temperature section increased from 854°C to 927°C, and the bottom temperature increased from 841°C to 1018°C, which took 0.7 to 0.9 minutes; The top temperature of the strong oxidation section increased from 927°C to 1105°C, and the bottom temperature increased from 1018°C to 1148°C, which took 1.5 to 1.8 minutes; The top temperature of the second front temperature section dropped from 1105°C to 1030°C, and then increased from 1030°C to 1080°C, and the bottom temperature dropped from 1148°C to 1047°C, and then increased from 1047°C to 1090°C, which took 2.9 to 3 minutes; The top temperature of the medium temperature section rises from 1080°C to 1194°C, and the bottom temperature rises from 1090°C to 1205°C, which takes 5.5 to 5.8 minutes; The top temperature of the high temperature section increased from 1194°C to 1204°C, and the bottom temperature increased from 1205°C to 1223°C, which took 4.5 to 5 minutes; The top temperature of the transition section drops from 1204°C to 950°C, and the bottom temperature drops from 1223°C to 950°C, which takes 2 to 2.1 minutes; The top temperature of the quenching section drops from 950°C to 584°C, and the bottom temperature drops from 950°C to 586°C, which takes 2 to 2.5 minutes; The top temperature of the slow cooling section dropped from 584° C. to 97° C., and the bottom temperature dropped from 586° C. to 97° C., which took 11 to 11.6 minutes.

[0017] The technical solution provided by the present invention may include the following beneficial effects: 1. In this technical solution, the quaternary composite flux of low eutectic K2O-Na2O-MgO-CaO is produced by the joint action of five raw materials, namely magnesia soil, waste brick powder, pyrophyllite, sodium feldspar and mixed mud. The above-mentioned quaternary composite flux can make the green body layer form a liquid phase in advance at a lower temperature. Due to the viscous flow and surface tension of the liquid phase, it can fill the gaps inside the green body layer in advance, prompting the particles to rearrange, approach each other and bond to each other as a whole. In addition, the alkaline oxide gradually enters the liquid phase, so that the amount of liquid phase generated under the action of the quaternary composite flux gradually increases, and gradually appears in the green body layer in a step-by-step manner, and gradually dissolves other substances, making the green body layer more compact, which is beneficial to the rock board to achieve the purpose of reducing the firing temperature and shortening the firing cycle. In addition, the waste brick powder is a clinker that has been fired. When the clinker is added to the raw materials composed of other raw materials, it can promote the rapid burning of the green body layer, further reduce the production energy consumption of the rock board, and effectively promote the rapid firing of the rock board and shorten the firing cycle. That is, through the above-mentioned multiple effects, the present application reduces the firing temperature of the rock slab to 1223°C and the firing cycle to 35 to 38 minutes, thereby achieving the purpose of lowering the firing temperature and shortening the firing cycle.

[0018] 2. Waste brick powder contains not only glass phase, but also mullite crystals. Through scanning electron microscope observation and phase positioning analysis, it can be clearly observed that mullite crystals are interspersed in the glass phase. In addition, the chemical composition of waste brick powder includes Al2O3 and SiO2, and the content of SiO2 in waste brick powder is 65-66%, and the content of Al2O3 is 18-19%, which belongs to the category of medium-silicon raw materials in aluminum (referring to raw materials with Al2O3 content of 13-20% and SiO2 content of 65-75% calculated by mass percentage). The above moderate silicon and aluminum content is conducive to promoting the uniform precipitation and growth of mullite crystals generated by the reaction of Al2O3 and SiO2 in waste brick powder in the glass phase. Therefore, when waste brick powder is added to the raw materials of the green body layer, the dispersibility of mullite crystals in the glass phase can be effectively improved. In addition, the waste brick powder itself has undergone multiple processes such as mixing, ball milling, firing and crushing, and when the green body layer raw materials are used, the green body layer raw materials generally need to go through the above processes again, so that the dispersion of each phase in the waste brick powder can be further optimized, further promoting the uniform dispersion of mullite crystals in the glass phase.

[0019] 3. The chemical composition of pyrophyllite, albite and mixed mud all contain Al2O3 and SiO2, and the main mineral component of the existing mixed mud is kaolinite. During the calcination process, Al2O3 and SiO2 in pyrophyllite, albite and kaolinite can react to form mullite. Therefore, Al2O3 and SiO2 in pyrophyllite, albite and mixed mud can all participate in the formation reaction of mullite under calcination conditions. In addition, the three raw materials of pyrophyllite, albite and mixed mud all belong to the category of silicon raw materials in aluminum, and the above moderate silicon-aluminum content is conducive to promoting the uniform precipitation and growth of mullite crystals generated by the reaction of Al2O3 and SiO2 in the above raw materials in the glass phase. DETAILED DESCRIPTION

[0020] The technical solution provides a cutting and cracking resistant rock board, comprising a body layer, a base glaze layer, a decorative layer and a polishing glaze layer arranged in sequence from bottom to top; Calculated by weight, the raw materials of the green body layer include: 1-3 parts of bentonite, 3-5 parts of magnesia clay, 22-28 parts of waste brick powder, 11-15 parts of washed mud, 28-35 parts of pyrophyllite, 12-16 parts of albite and 8-12 parts of mixed mud; The chemical components of the waste brick powder, the pyrophyllite, the albite and the mixed mud all include SiO2, Al2O3, Fe2O3, TiO2, CaO, MgO and K2O; Calculated by mass percentage, the content of SiO2 in the waste brick powder, the pyrophyllite, the albite and the mixed mud is 65-75%, and the content of Al2O3 is 13-20%; Calculated by mass percentage, the mineral components of the mixed mud include 50-60% kaolinite and 40-50% free quartz.

[0021] In order to solve the technical problems of high firing temperature, long firing time and poor cutting and cracking resistance of rock slabs in the prior art, the present technical solution proposes a cutting and cracking resistant rock slab. By optimizing the raw materials of the green body layer, the firing temperature of the rock slab is reduced to 1223°C, and the firing cycle is reduced to 35-38min. It has higher strength and cutting and cracking resistance. This allows the rock slab to improve its cutting and cracking resistance and strength while achieving low-temperature fast firing and reducing production energy consumption, so as to meet actual usage needs.

[0022] Specifically, the raw materials of the green body layer include bentonite, magnesia soil, waste brick powder, pyrophyllite, albite and mixed mud. Among them, the main mineral component of magnesia soil is talc, and magnesium oxide can be introduced into the formula system. The chemical components of waste brick powder, pyrophyllite, albite and mixed mud all include potassium oxide, sodium oxide, magnesium oxide and calcium oxide, so the above raw materials can also introduce potassium oxide, sodium oxide, magnesium oxide and calcium oxide into the formula system. Therefore, in the technical scheme, the low eutectic K2O-Na2O-MgO-CaO quaternary composite flux is produced by the joint action of the five raw materials of magnesia soil, waste brick powder, pyrophyllite, albite and mixed mud. The above quaternary composite flux can make the green body layer form a liquid phase in advance at a lower temperature. Due to the viscous flow and surface tension of the liquid phase, it can fill the gap inside the green body layer in advance, prompting the particles to rearrange, get close to each other and bond to each other as a whole. In addition, the alkaline oxide gradually enters the liquid phase, so that the amount of liquid phase generated under the action of the quaternary composite flux gradually increases, and gradually appears in the green body layer in a step-by-step manner, and gradually dissolves other substances, making the green body layer more compact, which is beneficial to the rock slab to achieve the purpose of reducing the firing temperature and shortening the firing cycle. In addition, waste brick powder is a clinker that has been fired. When the clinker is added to the raw materials composed of other raw materials, it can promote the rapid burning of the green body layer and further reduce the production energy consumption of the rock slab, thereby effectively promoting the rapid firing of the rock slab and shortening the firing cycle. That is, through the above-mentioned multi-faceted effects, the present application reduces the firing temperature of the rock slab to 1223°C, and the firing cycle is reduced to 35-38min, thereby achieving the purpose of reducing the firing temperature and shortening the firing cycle.

[0023] Secondly, waste brick powder contains not only glass phase, but also mullite crystals. Through scanning electron microscopy observation and phase positioning analysis, it can be clearly observed that mullite crystals are interspersed in the glass phase. In addition, the chemical composition of waste brick powder includes Al2O3 and SiO2, and the content of SiO2 in waste brick powder is 65-66%, and the content of Al2O3 is 18-19%, which belongs to the category of medium-silicon raw materials in aluminum (referring to raw materials with Al2O3 content of 13-20% and SiO2 content of 65-75% calculated by mass percentage). The above moderate silicon and aluminum content is conducive to promoting the uniform precipitation and growth of mullite crystals generated by the reaction of Al2O3 and SiO2 in waste brick powder in the glass phase. Therefore, when waste brick powder is added to the raw materials of the green body layer, the dispersibility of mullite crystals in the glass phase can be effectively improved. In addition, the waste brick powder itself has undergone multiple processes such as mixing, ball milling, firing and crushing, and when the green body layer raw materials are used, the green body layer raw materials generally need to go through the above processes again, so that the dispersion of each phase in the waste brick powder can be further optimized, further promoting the uniform dispersion of mullite crystals in the glass phase.

[0024] In addition, the chemical composition of pyrophyllite, albite and mixed mud all contain Al2O3 and SiO2, and the main mineral component of existing mixed mud is kaolinite. During the calcination process, Al2O3 and SiO2 in pyrophyllite, albite and kaolinite can react to generate mullite. Therefore, Al2O3 and SiO2 in pyrophyllite, albite and mixed mud can all participate in the formation reaction of mullite under calcination conditions. In addition, pyrophyllite, albite and mixed mud, these three raw materials, all belong to the category of silicon raw materials in aluminum, and the above-mentioned moderate silicon-aluminum content is conducive to promoting the uniform precipitation and growth of mullite crystals generated by the reaction of Al2O3 and SiO2 in the above-mentioned raw materials in the glass phase.

[0025] Therefore, through the above-mentioned multi-faceted effects, this technical solution makes the mullite crystals in the blank layer evenly dispersed in the glass phase, which not only effectively reduces the stress concentration points in the glass phase (i.e., potential defect areas), but also greatly hinders the cracking tendency of the glass phase, thereby significantly improving the cutting crack resistance of the rock plate. In addition, the uniform distribution of mullite crystals also significantly improves the thermal stability of the material, which is beneficial for the rock plate to better cope with thermal stress during temperature changes, reduces the risk of cracks caused by uneven thermal expansion and contraction, and is also beneficial to improving the cutting crack resistance.

[0026] Furthermore, in the existing K2O and Na2O fluxing system, when the calcination temperature reaches the lowest eutectic point, the amount of liquid phase that appears is very small. However, when the calcination temperature reaches the lowest eutectic point, a large amount of liquid phase will immediately appear, and it will rapidly increase with the increase in temperature. The rapid appearance of a large amount of liquid phase may make the stress distribution inside the green body layer uneven, affecting the anti-cutting cracking performance of the rock plate. However, the green body layer in the present technical solution adopts the K2O-Na2O-MgO-CaO quaternary composite flux, so that the liquid phase produced when the raw materials are melted is stepped, and it is a continuous step, which makes the green body layer more dense, and is also conducive to improving the anti-cutting cracking performance of the rock plate.

[0027] In summary, this technical solution effectively improves the cutting and cracking resistance of the rock slab by improving the dispersion of mullite crystals in the glass phase and enhancing the density of the green body layer.

[0028] It should be noted that mullite crystals have high strength and good thermal stability, and their uniform distribution can enhance the internal structure of the rock slab, thereby improving the overall strength of the rock slab; at the same time, the enhancement of the density of the green body layer can reduce pores and defects, improve the overall structural integrity of the material, and further enhance the strength of the rock slab; in addition, the four raw materials SiO2 and Al2O3 of waste brick powder, talc, albite and mixed mud are conducive to promoting the formation of more mullite crystals, further enhancing the overall strength of the rock slab.

[0029] Furthermore, the raw materials of the green body layer also include bentonite and washed mud. Among them, bentonite can be closely combined with other raw material particles to form a stable bonding structure, which has a positive effect on improving the strength of the rock board; washed mud has been purified, and its internal structure is more compact, and the bonding force between particles is enhanced, which also helps to improve the strength of the rock board.

[0030] In summary, this technical solution effectively improves the overall strength of the rock slab through the comprehensive play of multiple effects. It should be noted that bentonite has extremely high adsorption, expansion and dispersibility, so that the raw materials of the green body layer can form a stable suspension in water, with good thixotropy and lubricity, thereby increasing the plasticity of the green body layer; the clay particles in the washed mud will undergo flocculation under the action of water, so that a kind of colloidal connection is formed between the raw materials of the green body layer, thereby increasing the plasticity of the green body layer, and the plastic component of the washed mud is conducive to enhancing the formability and stability of the green body layer; further, the mixed mud is a mixture of soil or minerals with different components and properties. The clay particles in the mixed mud will also undergo flocculation under the action of water, so that a kind of colloidal connection is formed between the raw materials of the green body layer, thereby increasing the plasticity of the green body layer. At the same time, the strength of the mixed mud is usually high, which is conducive to ensuring the strength of the green body layer after drying, and thus is also conducive to improving its overall plasticity. Therefore, this technical solution improves the plasticity of the green body layer through the mutual cooperation of the three raw materials of bentonite, washed mud and mixed mud.

[0031] Finally, according to the weight percentage, the raw materials of the green body layer include: 1-3 parts of bentonite, 3-5 parts of magnesia clay, 22-28 parts of waste brick powder, 11-15 parts of washed mud, 28-35 parts of pyrophyllite, 12-16 parts of albite and 8-12 parts of mixed mud. By limiting the components in the raw materials of the green body layer, it is beneficial for each raw material to give full play to its own advantages, thereby ensuring the performance of the rock board.

[0032] It should be noted that the prior art uses washed mud and bauxite in combination to increase the aluminum content in the formula, while the mineral component of bauxite is mainly diaspore, and diaspore will decompose during the firing process to produce corundum α-Al2O3, while the reactivity of corundum is low, and it is difficult to melt or react with other raw materials in the formula, resulting in pores in the system, thus affecting the anti-cutting cracking performance. The sintering temperature of diaspore is relatively high, which is not conducive to the overall sintering process. Therefore, in order to meet the requirements of anti-cutting cracking performance in ultra-high use places, the present technical solution uses mixed mud whose mineral component is mainly kaolinite instead of bauxite, and uses washed mud and mixed mud in combination with each other, which is beneficial to improve the anti-cutting cracking performance under the premise of achieving low-temperature fast firing.

[0033] Furthermore, in order to improve the whiteness of the product and reduce costs in the prior art, yellow sand is usually added to the formula, but the mineral composition of yellow sand is mainly free quartz, and free quartz, as a relatively sensitive crystal, is prone to phase change during the cooling of the rock plate, accompanied by volume changes, thereby generating tiny cracks and affecting the anti-cutting cracking performance. Therefore, in order to meet the requirements of using ultra-high anti-cutting cracking performance in the use place, the present technical solution replaces the yellow sand with pyrophyllite with higher whiteness, and according to the previous description, the Al2O3 and SiO2 of the pyrophyllite can react to generate mullite crystals uniformly dispersed in the glass phase, which is beneficial to improve the anti-cutting cracking performance.

[0034] Preferably, calculated by mass percentage, the chemical composition of the bentonite includes SiO2 68-70%, Al2O3 14.5-15%, Fe2O3 0.8-0.9%, TiO2 0.1-0.2%, CaO 1.4-1.6%, MgO 1.5-1.6%, K2O 2.9-3% and Na2O 1.6-1.7%, and the rest is loss on ignition.

[0035] The present technical solution preferably adds magnesia clay with a CaO content of 0.7-0.8%, a MgO content of 19.5-20%, a K2O content of 0.2-0.3%, and a Na2O content of 0.2-0.3% calculated by mass percentage to the raw materials of the green body layer, which is beneficial to increase the content of flux in the formula system under the premise of avoiding excessive flux in the formula, which leads to the green body layer being easy to soften and deform during the firing process, so as to achieve the purpose of lowering the firing temperature and shortening the firing cycle. At the same time, the SiO2 content in bentonite is as high as 68-70%, and the Al2O3 content is 14.5-15%, which is beneficial to increase the silicon content in the formula, thereby improving the overall strength of the rock plate. In addition, it should be noted that bentonite is classified according to the content of Al2O3 and SiO2, and it does belong to the category of medium-aluminum medium-silicon raw materials. However, the mineral component of bentonite is mainly montmorillonite, which has a specific layered structure, which makes Al2O3 and SiO2 tightly combined with specific chemical bonds and arrangements, resulting in the difficulty of separating Al2O3 and SiO2 in bentonite and recombining them into mullite crystals during the sintering process. In other words, although bentonite contains chemical components that can react to form mullite, it is difficult to form mullite crystals due to the particularity of its mineral composition and structure.

[0036] Preferably, calculated by mass percentage, the chemical composition of the bentonite includes SiO2 68.45%, Al2O3 14.57%, Fe2O3 0.81%, TiO2 0.11%, CaO 1.48%, MgO 1.59%, K2O 2.91%, Na2O 1.67%, and the rest is loss on ignition.

[0037] It is further explained that, calculated by mass percentage, the chemical composition of the waste brick powder includes SiO2 65-66%, Al2O3 18-19%, Fe2O3 1.7-1.8%, TiO2 0.50-1%, CaO 0.5-0.7%, MgO 1.7-1.8%, K2O 1.9-2% and Na2O 2-2.1%, and the rest is loss on ignition; The particle size of the waste brick powder is ≤0.85 mm.

[0038] The technical solution preferably adds waste brick powder with a CaO content of 0.5-0.7%, a MgO content of 1.7-1.8%, a K2O content of 1.9-2%, and a Na2O content of 2-2.1% calculated by mass percentage to the raw materials of the green body layer, which is beneficial to increase the content of flux in the formula under the premise of avoiding excessive flux in the formula, which leads to the green body layer being easily softened and deformed during the firing process, so as to achieve the purpose of reducing the firing temperature and shortening the firing cycle. At the same time, the SiO2 content in the waste brick powder is as high as 65-66%, and the Al2O3 content is as high as 18-19%, which is beneficial to increase the content of silicon and aluminum in the formula, thereby improving the strength of the rock board.

[0039] Furthermore, by limiting the particle size of waste brick powder, it is not only beneficial to improve its utilization rate, but also to further optimize the dispersion of various phases in the waste brick powder, further promote the uniform dispersion of mullite crystals in the glass phase, and further improve the cutting resistance of the rock board. In addition, it can also ensure that the waste brick powder can better fill the tiny pores of the green body layer, enhance the density and strength of the rock board, and also help improve the cutting resistance of the rock board.

[0040] Preferably, calculated by mass percentage, the chemical composition of the waste brick powder includes SiO2 65.67%, Al2O3 18.50%, Fe2O3 1.75%, TiO2 0.50%, CaO 0.62%, MgO 1.77%, K2O 1.92%, Na2O 2.09%, and the rest is loss on ignition.

[0041] It is further explained that, calculated by mass percentage, the chemical composition of the pyrophyllite includes SiO2 70-73%, Al2O3 18-20%, Fe2O3 0.5-0.8%, TiO2 0.4-0.5%, CaO 0.2-0.3%, MgO 0.1-0.2%, K2O 2.3-2.4% and Na2O 0.1-0.2%, and the rest is loss on ignition.

[0042] The technical solution preferably adds pyrophyllite with a CaO content of 0.2-0.3%, a MgO content of 0.1-0.2%, a K2O content of 2.3-2.4%, and a Na2O content of 0.1-0.2% calculated by mass percentage to the raw materials of the green body layer, which is beneficial to increase the content of flux in the formula under the premise of avoiding excessive flux in the formula, which leads to the green body layer being easily softened and deformed during the firing process, so as to achieve the purpose of reducing the firing temperature and shortening the firing cycle. At the same time, the SiO2 content in pyrophyllite is as high as 70-73%, and the Al2O3 content is as high as 18-20%, which is beneficial to increase the content of silicon and aluminum in the formula, thereby improving the strength of the rock plate.

[0043] Preferably, calculated by mass percentage, the chemical composition of the pyrophyllite includes SiO2 72.54%, Al2O3 18.23%, Fe2O3 0.79%, TiO2 0.46%, CaO 0.24%, MgO 0.13%, K2O 2.31%, Na2O 0.16%, and the rest is loss on ignition.

[0044] It is further explained that, calculated by mass percentage, the chemical composition of the albite includes SiO2 68-70%, Al2O3 16-18%, Fe2O3 0.1-0.2%, TiO2 0.05-0.1%, CaO 0.5-0.6%, MgO 0.1-0.2%, K2O 0.6-0.7% and Na2O 8-8.1%, and the rest is loss on ignition.

[0045] The technical solution preferably adds albite with a CaO content of 0.5-0.6%, a MgO content of 0.1-0.2%, a K2O content of 0.6-0.7%, and a Na2O content of 8-8.1% calculated by mass percentage to the raw materials of the green body layer, which is beneficial to increase the content of flux in the formula under the premise of avoiding excessive flux in the formula, which leads to the green body layer being easily softened and deformed during the firing process, so as to achieve the purpose of reducing the firing temperature and shortening the firing cycle. At the same time, the SiO2 content in albite is as high as 68-70%, and the Al2O3 content is as high as 16-18%, which is beneficial to increase the content of silicon and aluminum in the formula, thereby improving the strength of the rock plate.

[0046] Preferably, calculated by mass percentage, the chemical composition of the albite includes SiO2 68.7%, Al2O3 16.46%, Fe2O3 0.19%, TiO2 0.09%, CaO 0.54%, MgO 0.11%, K2O 0.66%, Na2O 8.01%, and the rest is loss on ignition.

[0047] It is further explained that, calculated by mass percentage, the chemical composition of the mixed mud includes SiO2 70-70.5%, Al2O3 19-20%, Fe2O3 1-1.2%, TiO2 0.3-0.4%, CaO 0.4-0.5%, MgO 0.2-0.3%, K2O 1-1.1% and Na2O 0.2-0.3%, and the rest is loss on ignition.

[0048] The technical solution preferably adds a mixed mud with a CaO content of 0.4-0.5%, a MgO content of 0.2-0.3%, a K2O content of 1-1.1%, and a Na2O content of 0.2-0.3% calculated by mass percentage to the raw materials of the green body layer, which is beneficial to increase the content of flux in the formula under the premise of avoiding excessive flux in the formula, which leads to the green body layer being easily softened and deformed during the firing process, so as to achieve the purpose of reducing the firing temperature and shortening the firing cycle. At the same time, the content of SiO2 in the mixed mud is as high as 70-70.5%, and the content of Al2O3 is as high as 19-20%, which is beneficial to increase the content of silicon and aluminum in the formula, thereby improving the strength of the rock plate.

[0049] Preferably, calculated by mass percentage, the chemical composition of the mixed mud includes SiO2 70.09%, Al2O3 19.07%, Fe2O3 1.15%, TiO2 0.39%, CaO 0.4%, MgO 0.24%, K2O 1.09%, Na2O 0.2%, and the rest is loss on ignition.

[0050] It is further explained that, calculated by mass percentage, the chemical composition of the washed mud includes SiO2 50-53%, Al2O3 31-33%, Fe2O3 1.4-1.5%, TiO2 0.1-0.2%, CaO 0.1-0.2%, MgO 0.2-0.3%, K2O 3-3.2% and Na2O 0.3-0.4%, and the rest is loss on ignition.

[0051] The present technical solution preferably adds washed mud with a SiO2 content of 50-53% and an Al2O3 content of 31-33% calculated by mass percentage, and a mineral component of kaolinite to the raw material of the green body layer, which is beneficial to the reaction of SiO2 and Al2O3 in the washed mud to form mullite during the calcination process, thereby increasing the content of mullite and the distribution of mullite in the glass phase, thereby improving the anti-cutting cracking performance and strength. It should be noted that the main mineral component of the washed mud is kaolinite.

[0052] Preferably, calculated by mass percentage, the chemical composition of the washed mud includes SiO2 52.27%, Al2O3 32.5%, Fe2O3 1.41%, TiO2 0.18%, CaO 0.12%, MgO 0.25%, K2O 3.16%, Na2O 0.37%, and the rest is loss on ignition.

[0053] It is further explained that, calculated by mass percentage, the chemical composition of the magnesia soil includes SiO2 62-63%, Al2O3 5.7-5.8%, Fe2O3 1.6-1.7%, TiO2 0.1-0.2%, CaO 0.7-0.8%, MgO 19.5-20%, K2O 0.2-0.3% and Na2O 0.2-0.3%, and the rest is loss on ignition.

[0054] The present technical solution preferably adds magnesia soil with a CaO content of 0.7-0.8%, a MgO content of 19.5-20%, a K2O content of 0.2-0.3%, and a Na2O content of 0.2-0.3% to the raw materials of the green body layer, which is beneficial to increase the content of flux in the formula system under the premise of avoiding excessive flux in the formula, which leads to the green body layer being easy to soften and deform during the firing process, so as to achieve the purpose of reducing the firing temperature and shortening the firing cycle. At the same time, the content of SiO2 in magnesia soil is as high as 62-63%, which is beneficial to increase the content of silicon and aluminum in the formula, thereby facilitating the formation of more silicate crystals and further enhancing the overall strength of the rock plate. It should be noted that the mineral components of magnesia soil are mainly talc and free quartz, and the component silica in magnesia soil mainly exists in the form of free quartz, which is difficult to react with other components. Therefore, magnesia soil added to the formula does not tend to generate mullite crystals.

[0055] Preferably, calculated by mass percentage, the chemical composition of the magnesia soil includes SiO2 62.585%, Al2O3 5.79%, Fe2O3 1.615%, TiO2 0.13%, CaO 0.79%, MgO 19.5%, K2O 0.25%, Na2O 0.245%, and the rest is loss on ignition.

[0056] A method for preparing a cutting-resistant rock cracking plate, for preparing the cutting-resistant rock cracking plate, comprises the following steps: A. After mixing the formulated amount of bentonite, magnesia clay, waste brick powder, washed mud, pyrophyllite, albite and mixed mud evenly, adding water to ball mill and sieving to obtain slurry; spray granulating the slurry to obtain a blank; pressing the blank into shape, and drying to obtain a blank layer; wherein the fineness of the ball mill is a 325 mesh sieve, and the sieve residue is 1.3-1.8% calculated by mass percentage; B. Applying base glaze on the surface of the body layer to obtain a base glaze layer; C. Printing color ink on the surface of the base glaze layer according to a preset pattern to obtain a decorative layer; D. Apply glaze on the surface of the decorative layer to obtain a glaze layer; E. After drying, the material is put into a kiln for firing to obtain a cutting-resistant rock board; wherein the firing temperature of the cutting-resistant rock board is ≤1223°C, and the firing cycle is 35 to 38 minutes.

[0057] The technical solution also proposes a method for preparing a cutting-resistant rock plate, which is simple and easy to operate, and is conducive to ensuring the relevant performance of the rock plate during the preparation process. It should be noted that the base glaze layer in the technical solution is formed by applying the conventional base glaze in the ceramic field, the decorative layer is printed by printing the conventional color ink in the ceramic field, and the polishing glaze layer is formed by applying the conventional polishing glaze in the ceramic field. The base glaze, color ink and polishing glaze are not further described here.

[0058] Specifically, in the present technical solution, when preparing the slurry, the fineness of the ball mill is limited to a 325 mesh sieve, and the sieve residue is limited to 1.3-1.8%. By controlling the ball mill fineness and sieve residue, it is not only beneficial to the smooth progress of the subsequent screening operation, but also beneficial to make the chemical reaction of the raw materials in the formula more thorough during the calcination process, so that the gaseous products are fully decomposed, and the generation of impurity phases and voids is effectively reduced, which is more conducive to the formation of a more uniform microstructure, thereby improving the anti-cutting cracking performance.

[0059] To further illustrate, in step A, the specific method of screening is: filtering the raw materials of the green body layer after water ball milling using a 40-mesh sieve, a 60-mesh sieve, and an 80-mesh sieve in sequence, and then filtering twice using a 110-mesh sieve.

[0060] The raw material of the green body layer after water ball milling contains particles of different particle sizes. Direct filtration with a 110-mesh screen is prone to clogging of the screen, affecting production efficiency. Therefore, the technical solution adopts a graded filtration strategy, specifically: use a 40-mesh screen to filter to remove coarse particles with a particle size greater than 0.364 mm; then, use a 60-mesh screen to further filter to remove particles with a particle size greater than 0.245 mm; then, use an 80-mesh screen to continue filtering to remove particles with a particle size greater than 0.185 mm; finally, filter twice through a 110-mesh screen to ensure that all particles with a particle size greater than 0.145 mm are removed. The above series of filtration steps effectively reduce the coarse particle content in the slurry, allowing the green body layer to react more fully during high-temperature firing, avoiding defects or gaps due to coarse particles, thereby reducing the generation of cracking points and improving anti-cutting cracking performance.

[0061] In addition, the reason for choosing a 110-mesh sieve to filter twice is that: on the one hand, the sieve may be damaged in an imperceptible manner during use. Although there are regular inspection measures, double filtration can further ensure that there is no particle mixing caused by a damaged sieve; on the other hand, when the sieve mesh number exceeds 110 mesh, the filtration efficiency will drop significantly, affecting the overall production capacity.

[0062] Further, in step E, the firing curve of the anti-cutting and cracking rock plate includes a preheating section, a first pre-temperature section, a strong oxidation section, a second pre-temperature section, a medium temperature section, a high temperature section, a transition section, a rapid cooling section and a slow cooling section; The top temperature of the preheating section rises from room temperature to 854°C, and the bottom temperature rises from room temperature to 841°C, which takes 5 to 5.4 minutes; The top temperature of the first pre-temperature section increased from 854°C to 927°C, and the bottom temperature increased from 841°C to 1018°C, which took 0.7 to 0.9 minutes; The top temperature of the strong oxidation section increased from 927°C to 1105°C, and the bottom temperature increased from 1018°C to 1148°C, which took 1.5 to 1.8 minutes; The top temperature of the second front temperature section dropped from 1105°C to 1030°C, and then increased from 1030°C to 1080°C, and the bottom temperature dropped from 1148°C to 1047°C, and then increased from 1047°C to 1090°C, which took 2.9 to 3 minutes; The top temperature of the medium temperature section rises from 1080°C to 1194°C, and the bottom temperature rises from 1090°C to 1205°C, which takes 5.5 to 5.8 minutes; The top temperature of the high temperature section increased from 1194°C to 1204°C, and the bottom temperature increased from 1205°C to 1223°C, which took 4.5 to 5 minutes; The top temperature of the transition section drops from 1204°C to 950°C, and the bottom temperature drops from 1223°C to 950°C, which takes 2 to 2.1 minutes; The top temperature of the quenching section drops from 950°C to 584°C, and the bottom temperature drops from 950°C to 586°C, which takes 2 to 2.5 minutes; The top temperature of the slow cooling section dropped from 584° C. to 97° C., and the bottom temperature dropped from 586° C. to 97° C., which took 11 to 11.6 minutes.

[0063] This technical solution innovatively adds a strong oxidation section between the first pre-temperature section and the second pre-temperature section. The strong oxidation section uses high temperature to quickly burn the high decomposition temperature substances (substances with decomposition temperatures in the range of 1050-1100°C) in the raw materials of the green body layer, effectively promoting the decomposition and discharge of the above substances, thereby reducing their residues in the product, thereby reducing the porosity, avoiding stress concentration during cutting, and improving the anti-cutting cracking performance. At the same time, the introduction of the strong oxidation section also helps to reduce the pores caused by the residues of substances such as carbonates and sulfates, further enhancing the anti-cutting cracking performance.

[0064] Since the firing cycle is relatively fixed, if the sum of the time of the first pre-temperature stage, the strong oxidation stage and the second pre-temperature stage is too long, the medium temperature, high temperature stage and cooling stage will be shortened in disguise, thus affecting the quality of the product. Therefore, this technical solution strictly controls the total time of the first pre-temperature stage, the strong oxidation stage and the second pre-temperature stage to not exceed 7 minutes, thereby ensuring the various performances of the product under the premise of rapid firing.

[0065] In addition, this technical solution also optimizes the duration of the rapid cooling section and the slow cooling section. The rapid cooling section lasts more than 2 minutes, while the slow cooling section lasts more than 10 minutes, aiming to slow down the cooling rate, thereby reducing the phase change rate of free quartz in the green body layer, reducing microcracks caused by volume changes, and effectively improving the anti-cutting cracking performance.

[0066] Furthermore, due to the difference in shrinkage rates between the glaze layer (top layer) and the body layer (bottom layer) during the firing process, the rock slab is prone to concave or convex deformation. In addition, insufficient oxidation inside the body layer can easily lead to black heart oxidation, and black heart oxidation is usually related to the temperature distribution at the top and bottom of the pre-temperature section of the firing curve. Therefore, the present application limits the bottom temperature and top temperature of each stage in the firing curve, which is not only conducive to avoiding deformation of the calcined rock slab, thereby ensuring its flatness, but also helps to avoid black heart oxidation inside the rock slab and ensure its quality.

[0067] It is worth noting that the firing temperature of the rock slab refers to its maximum calcination temperature. Therefore, the firing temperature of the rock slab in this technical solution is as low as 1223°C. Compared with the traditional process, this firing temperature is lower, but it can still meet the product performance requirements.

[0068] The technical solution of the present invention is further illustrated below through specific implementation methods.

[0069] Performance Test: Anti-cutting crack performance: Take 4 calcined rock slabs to obtain 4 rock slabs to be tested with a specification of 1500×750mm (i.e. length 1500mm, width 750mm). Cut the 4 rock slabs to be tested 10 times along the length direction, and the cutting interval is 10mm. If the 4 rock slabs to be tested do not have edge collapse during the cutting process, the anti-cutting crack performance is qualified.

[0070] Modulus of rupture: The modulus of rupture of the rock slab is tested in accordance with GB / T 3810.4-2016 Test methods for ceramic tiles Part 4: Determination of modulus of rupture and breaking strength.

[0071] Destructive strength: The destructive strength of the rock slab is tested in accordance with "GB / T 3810.4-2016 Ceramic Tile Test Method Part 4: Determination of Rupture Modulus and Destructive Strength".

[0072] In the embodiments and comparative examples of the present invention, the chemical composition of the waste brick powder includes SiO2 65.67%, Al2O3 18.50%, Fe2O3 1.75%, TiO2 0.50%, CaO 0.62%, MgO 1.77%, K2O 1.92%, Na2O 2.09%, and the rest is loss on ignition. According to the mass percentage, the chemical composition of pyrophyllite includes SiO272.54%, Al2O318.23%, Fe2O30.79%, TiO20.46%, CaO 0.24%, MgO 0.13%, K2O 2.31%, Na2O 0.16%, and the rest is the loss on ignition; Calculated by mass percentage, the chemical composition of albite includes SiO268.7%, Al2O316.46%, Fe2O30.19%, TiO20.09%, CaO 0.54%, MgO 0.11%, K2O 0.66%, Na2O 8.01%, and the rest is loss on ignition; Calculated by mass percentage, the mineral composition of the mixed mud includes 60% kaolinite and 40% free quartz; and calculated by mass percentage, the chemical composition of the mixed mud includes SiO270.09%, Al2O319.07%, Fe2O31.15%, TiO20.39%, CaO 0.4%, MgO 0.24%, K2O 1.09%, Na2O 0.2%, and the rest is loss on ignition; Calculated by mass percentage, the chemical composition of the washed mud includes SiO252.27%, Al2O332.5%, Fe2O31.41%, TiO20.18%, CaO 0.12%, MgO 0.25%, K2O 3.16%, Na2O 0.37%, and the rest is loss on ignition; According to the mass percentage, the chemical composition of magnesia soil includes SiO262.585%, Al2O35.79%, Fe2O31.615%, TiO20.13%, CaO 0.79%, MgO 19.5%, K2O 0.25%, Na2O 0.245%, and the rest is loss on ignition; Calculated by mass percentage, the chemical composition of bentonite includes SiO2 68.45%, Al2O3 14.57%, Fe2O3 0.81%, TiO2 0.11%, CaO 1.48%, MgO 1.59%, K2O 2.91%, Na2O 1.67%, and the rest is loss on ignition.

[0073] In addition, if no specific techniques or conditions are specified in the examples and comparative examples, the techniques or conditions described in the literature in the field or the product instructions are used. If the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be purchased commercially.

[0074] Example 1 A. 1 part of bentonite, 4 parts of magnesia clay, 26 parts of waste brick powder with a particle size of 0.7 mm, 13 parts of washed mud, 30 parts of pyrophyllite, 14 parts of albite and 10 parts of mixed mud are mixed evenly, and then ball-milled and sieved to obtain a slurry; the slurry is spray-granulated to obtain a blank; the blank is pressed into shape, and dried to obtain a blank layer; wherein the fineness of the ball milling is a 325-mesh sieve, and the sieve residue is 1.3% calculated by mass percentage; the specific method of sieving is: the raw material of the blank layer after the water-added ball milling is filtered once through a 40-mesh sieve, a 60-mesh sieve, and an 80-mesh sieve, and then filtered twice through a 110-mesh sieve; B. Applying base glaze on the surface of the body layer to obtain a base glaze layer; C. Printing color ink on the surface of the base glaze layer according to a preset pattern to obtain a decorative layer; D. Apply glaze on the surface of the decorative layer to obtain a glaze layer; E. After drying, the plate is fired in a kiln to obtain a cutting-resistant cracking rock plate; wherein the firing curve of the cutting-resistant cracking rock plate includes a preheating section, a first pre-temperature section, a strong oxidation section, a second pre-temperature section, a medium temperature section, a high temperature section, a transition section, a rapid cooling section and a slow cooling section; the top temperature of the preheating section rises from room temperature to 854°C, and the bottom temperature rises from room temperature to 841°C, which takes 5.41 minutes; the top temperature of the first pre-temperature section rises from 854°C to 927°C, and the bottom temperature rises from 841°C to 1018°C, which takes 0.83 minutes; the top temperature of the strong oxidation section rises from 927°C to 1105°C, and the bottom temperature rises from 1018°C to 1148°C, which takes 1.66 minutes; the top temperature of the second pre-temperature section drops from 1105°C to 1030°C, and then rises from 1030°C to 1080°C, and the bottom temperature drops from 1148°C to 1080°C. To 1047℃, and then from 1047℃ to 1090℃, it takes 2.92min; the top temperature of the medium temperature section rises from 1080℃ to 1194℃, and the bottom temperature rises from 1090℃ to 1205℃, which takes 5.8min; the top temperature of the high temperature section rises from 1194℃ to 1204℃, and the bottom temperature rises from 1205℃ to 1223℃, which takes 4.99min; the top temperature of the transition section drops from 1204℃ to 950℃, and the bottom temperature drops from 1223℃ to 950℃, which takes 2.08min; the top temperature of the rapid cooling section drops from 950℃ to 584℃, and the bottom temperature drops from 950℃ to 586℃, which takes 2.5min; the top temperature of the slow cooling section drops from 584℃ to 97℃, and the bottom temperature drops from 586℃ to 97℃, which takes 11.6min.

[0075] Example 2 A. After 2 parts of bentonite, 3 parts of magnesia clay, 22 parts of waste brick powder with a particle size of 0.8 mm, 15 parts of washed mud, 28 parts of pyrophyllite, 16 parts of albite and 10 parts of mixed mud are mixed evenly, the mixture is ball-milled with water and sieved to obtain a slurry; the slurry is spray-granulated to obtain a blank; the blank is pressed into shape, and the blank layer is obtained after drying; wherein the fineness of the ball milling is a 325-mesh sieve, and the sieve residue is 1.5% calculated by mass percentage; the specific method of sieving is: the raw materials of the blank layer after the water-added ball milling are filtered once through a 40-mesh sieve, a 60-mesh sieve, and an 80-mesh sieve in sequence, and then filtered twice through a 110-mesh sieve; B. Applying base glaze on the surface of the body layer to obtain a base glaze layer; C. Printing color ink on the surface of the base glaze layer according to a preset pattern to obtain a decorative layer; D. Apply glaze on the surface of the decorative layer to obtain a glaze layer; E. After drying, the material is put into a kiln for firing to obtain a cutting-resistant cracking rock plate; wherein the firing curve of the cutting-resistant cracking rock plate includes a preheating section, a first pre-temperature section, a strong oxidation section, a second pre-temperature section, a medium temperature section, a high temperature section, a transition section, a rapid cooling section and a slow cooling section; the top temperature of the preheating section rises from room temperature to 854°C, and the bottom temperature rises from room temperature to 841°C, which takes 5.2 minutes; the top temperature of the first pre-temperature section rises from 854°C to 927°C, and the bottom temperature rises from 841°C to 1018°C, which takes 0.8 minutes; the top temperature of the strong oxidation section rises from 927°C to 1105°C, and the bottom temperature rises from 1018°C to 1148°C, which takes 1.5 minutes; the top temperature of the second pre-temperature section drops from 1105°C to 1030°C, and then rises from 1030°C to 1080°C, and the bottom temperature rises from 1148°C to 1150°C. It dropped to 1047℃, and then increased from 1047℃ to 1090℃, which took 2.9 minutes; the top temperature of the medium temperature section increased from 1080℃ to 1194℃, and the bottom temperature increased from 1090℃ to 1205℃, which took 5.5 minutes; the top temperature of the high temperature section increased from 1194℃ to 1204℃, and the bottom temperature increased from 1205℃ to 1223℃, which took 4.5 minutes; the top temperature of the transition section dropped from 1204℃ to 950℃, and the bottom temperature dropped from 1223℃ to 950℃, which took 2 minutes; the top temperature of the rapid cooling section dropped from 950℃ to 584℃, and the bottom temperature dropped from 950℃ to 586℃, which took 2.5 minutes; the top temperature of the slow cooling section dropped from 584℃ to 97℃, and the bottom temperature dropped from 586℃ to 97℃, which took 11.2 minutes.

[0076] Example 3 A. 3 parts of bentonite, 5 parts of magnesia clay, 28 parts of waste brick powder with a particle size of 0.6 mm, 14 parts of washed mud, 32 parts of pyrophyllite, 15 parts of albite and 9 parts of mixed mud are mixed evenly, and then water is added to ball mill and sieved to obtain slurry; the slurry is spray granulated to obtain a blank; the blank is pressed into shape, and dried to obtain a blank layer; wherein the fineness of the ball milling is a 325-mesh sieve, and the sieve residue is 1.4% calculated by mass percentage; the specific method of sieving is: the raw material of the blank layer after water ball milling is filtered once through a 40-mesh sieve, a 60-mesh sieve, and an 80-mesh sieve, and then filtered twice through a 110-mesh sieve; B. Applying base glaze on the surface of the body layer to obtain a base glaze layer; C. Printing color ink on the surface of the base glaze layer according to a preset pattern to obtain a decorative layer; D. Apply glaze on the surface of the decorative layer to obtain a glaze layer; E. After drying, the plate is fired in a kiln to obtain a cutting-resistant cracking rock plate; wherein the firing curve of the cutting-resistant cracking rock plate includes a preheating section, a first pre-temperature section, a strong oxidation section, a second pre-temperature section, a medium temperature section, a high temperature section, a transition section, a rapid cooling section and a slow cooling section; the top temperature of the preheating section rises from room temperature to 854°C, and the bottom temperature rises from room temperature to 841°C, which takes 5.1 minutes; the top temperature of the first pre-temperature section rises from 854°C to 927°C, and the bottom temperature rises from 841°C to 1018°C, which takes 0.75 minutes; the top temperature of the strong oxidation section rises from 927°C to 1105°C, and the bottom temperature rises from 1018°C to 1148°C, which takes 1.5 minutes; the top temperature of the second pre-temperature section drops from 1105°C to 1030°C, and then rises from 1030°C to 1080°C, and the bottom temperature drops from 1148°C to 1080°C. To 1047℃, and then from 1047℃ to 1090℃, it takes 2.95min; the top temperature of the medium temperature section rises from 1080℃ to 1194℃, and the bottom temperature rises from 1090℃ to 1205℃, which takes 5.6min; the top temperature of the high temperature section rises from 1194℃ to 1204℃, and the bottom temperature rises from 1205℃ to 1223℃, which takes 4.8min; the top temperature of the transition section drops from 1204℃ to 950℃, and the bottom temperature drops from 1223℃ to 950℃, which takes 2.1min; the top temperature of the rapid cooling section drops from 950℃ to 584℃, and the bottom temperature drops from 950℃ to 586℃, which takes 2.3min; the top temperature of the slow cooling section drops from 584℃ to 97℃, and the bottom temperature drops from 586℃ to 97℃, which takes 11.3min.

[0077] Comparative Example 1 The preparation method and raw materials of Comparative Example 1 are the same as those of Example 1, except that no waste brick powder is added to the raw materials of the green body layer in Comparative Example 1.

[0078] Comparative Example 2 The preparation method and raw materials of Comparative Example 2 are the same as those of Example 1, except that pyrophyllite is not added to the raw materials of the green body layer in Comparative Example 2.

[0079] Comparative Example 3 The preparation method and raw materials of Comparative Example 3 are the same as those of Example 1, except that albite is not added to the raw materials of the green body layer in Comparative Example 3.

[0080] Comparative Example 4 The preparation method and raw materials of Comparative Example 4 are the same as those of Example 1, except that no mixed mud is added to the raw materials of the green body layer in Comparative Example 4.

[0081] The rock slabs were prepared by the preparation methods in the above-mentioned embodiments and comparative examples respectively, and the obtained rock slabs were tested for their anti-cutting cracking performance, rupture modulus and destructive strength. The results are shown in Table 1 below.

[0082] Table 1 Performance test results of different rock panels in the examples and comparative examples

[0083] From the performance test results of each embodiment in the above table, it can be seen that the rock slab prepared by the preparation method of this scheme can be fired under the firing conditions of a firing temperature as low as 1223°C and a firing cycle of 35 to 38 minutes, and there is no edge collapse, and the rupture modulus is ≥54MPa, the destructive strength is ≥2500N, and it has high strength and resistance to cutting cracks.

[0084] Since no waste brick powder was added in Comparative Example 1, no pyrophyllite was added in Comparative Example 2, no albite was added in Comparative Example 3, and no mixed mud was added in Comparative Example 4, the fluxing effect of the above raw materials could not be exerted, so that the slab could not be completely calcined, and the obtained slab contained sandwich raw materials, which affected the reduction of the anti-cutting cracking performance. At the same time, it also led to a reduction in the amount of mullite crystals uniformly dispersed in the glass phase, further leading to a reduction in the anti-cutting cracking performance and strength of the slab.

[0085] The technical principle of the present invention is described above in conjunction with specific embodiments. These descriptions are only for explaining the principle of the present invention and cannot be interpreted as limiting the scope of protection of the present invention in any way. Based on the explanations herein, those skilled in the art can associate other specific implementations of the present invention without paying creative labor, and these methods will fall within the scope of protection of the present invention.

Claims

1. A cutting and cracking resistant rock plate, characterized in that: It includes a body layer, a base glaze layer, a decorative layer and a polishing glaze layer which are arranged in sequence from bottom to top; Calculated by weight, the raw materials of the green body layer include: 1-3 parts of bentonite, 3-5 parts of magnesia clay, 22-28 parts of waste brick powder, 11-15 parts of washed mud, 28-35 parts of pyrophyllite, 12-16 parts of albite and 8-12 parts of mixed mud; The chemical components of the waste brick powder, the pyrophyllite, the albite and the mixed mud all include SiO2, Al2O3, Fe2O3, TiO2, CaO, MgO and K2O; Calculated by mass percentage, the content of SiO2 in the waste brick powder, the pyrophyllite, the albite and the mixed mud is 65-75%, and the content of Al2O3 is 13-20%; Calculated by mass percentage, the mineral components of the mixed mud include 50-60% kaolinite and 40-50% free quartz.

2. The anti-cutting rock cracking plate according to claim 1, characterized in that: Calculated by mass percentage, the chemical composition of the waste brick powder includes SiO2 65-66%, Al2O3 18-19%, Fe2O3 1.7-1.8%, TiO2 0.50-1%, CaO 0.5-0.7%, MgO 1.7-1.8%, K2O 1.9-2% and Na2O 2-2.1%, and the rest is loss on ignition; The particle size of the waste brick powder is ≤0.85 mm.

3. The anti-cutting rock cracking plate according to claim 1, characterized in that: Calculated by mass percentage, the chemical composition of the pyrophyllite includes SiO2 70-73%, Al2O3 18-20%, Fe2O3 0.5-0.8%, TiO2 0.4-0.5%, CaO 0.2-0.3%, MgO 0.1-0.2%, K2O 2.3-2.4% and Na2O 0.1-0.2%, and the rest is loss on ignition.

4. The anti-cutting rock cracking plate according to claim 1, characterized in that: Calculated by mass percentage, the chemical composition of the albite includes SiO2 68-70%, Al2O3 16-18%, Fe2O3 0.1-0.2%, TiO2 0.05-0.1%, CaO 0.5-0.6%, MgO 0.1-0.2%, K2O 0.6-0.7% and Na2O 8-8.1%, and the rest is loss on ignition.

5. The anti-cutting rock cracking plate according to claim 1, characterized in that: Calculated by mass percentage, the chemical composition of the mixed mud includes SiO2 70-70.5%, Al2O3 19-20%, Fe2O3 1-1.2%, TiO2 0.3-0.4%, CaO 0.4-0.5%, MgO 0.2-0.3%, K2O 1-1.1% and Na2O 0.2-0.3%, and the rest is loss on ignition.

6. The anti-cutting rock cracking plate according to claim 1, characterized in that: Calculated by mass percentage, the chemical composition of the washed mud includes SiO2 50-53%, Al2O3 31-33%, Fe2O3 1.4-1.5%, TiO2 0.1-0.2%, CaO 0.1-0.2%, MgO 0.2-0.3%, K2O 3-3.2% and Na2O 0.3-0.4%, and the rest is loss on ignition.

7. The anti-cutting rock cracking plate according to claim 1, characterized in that: Calculated by mass percentage, the chemical composition of the magnesia soil includes SiO2 62-63%, Al2O3 5.7-5.8%, Fe2O3 1.6-1.7%, TiO2 0.1-0.2%, CaO 0.7-0.8%, MgO 19.5-20%, K2O 0.2-0.3% and Na2O 0.2-0.3%, and the rest is loss on ignition.

8. A method for preparing a cutting-resistant rock plate, characterized in that: The method for preparing the anti-cutting rock cracking board according to any one of claims 1 to 7 comprises the following steps: A. After mixing the formulated amount of bentonite, magnesia clay, waste brick powder, washed mud, pyrophyllite, albite and mixed mud evenly, adding water to ball mill and sieving to obtain slurry; spray granulating the slurry to obtain a blank; pressing the blank into shape, and drying to obtain a blank layer; wherein the fineness of the ball mill is a 325 mesh sieve, and the sieve residue is 1.3-1.8% calculated by mass percentage; B. Applying base glaze on the surface of the body layer to obtain a base glaze layer; C. Printing color ink on the surface of the base glaze layer according to a preset pattern to obtain a decorative layer; D. Apply glaze on the surface of the decorative layer to obtain a glaze layer; E. After drying, the material is put into a kiln for firing to obtain a cutting-resistant rock board; wherein the firing temperature of the cutting-resistant rock board is ≤1223°C, and the firing cycle is 35 to 38 minutes.

9. The method for preparing a cutting-resistant rock plate according to claim 8, characterized in that: In step A, the specific method of screening is: filtering the raw material of the green body layer after water ball milling through a 40-mesh sieve, a 60-mesh sieve, and an 80-mesh sieve in sequence, and then filtering twice through a 110-mesh sieve.

10. The method for preparing a cutting-resistant rock plate according to claim 8, characterized in that: In step E, the firing curve of the anti-cutting and cracking rock plate includes a preheating section, a first pre-temperature section, a strong oxidation section, a second pre-temperature section, a medium temperature section, a high temperature section, a transition section, a rapid cooling section and a slow cooling section; The top temperature of the preheating section rises from room temperature to 854°C, and the bottom temperature rises from room temperature to 841°C, which takes 5 to 5.4 minutes; The top temperature of the first pre-temperature section increased from 854°C to 927°C, and the bottom temperature increased from 841°C to 1018°C, which took 0.7 to 0.9 minutes; The top temperature of the strong oxidation section rises from 927°C to 1105°C, and the bottom temperature rises from 1018°C to 1148°C, which takes 1.5 to 1.8 minutes; The top temperature of the second front temperature section dropped from 1105°C to 1030°C, and then increased from 1030°C to 1080°C, and the bottom temperature dropped from 1148°C to 1047°C, and then increased from 1047°C to 1090°C, which took 2.9 to 3 minutes; The top temperature of the medium temperature section rises from 1080°C to 1194°C, and the bottom temperature rises from 1090°C to 1205°C, which takes 5.5 to 5.8 minutes; The top temperature of the high temperature section increased from 1194°C to 1204°C, and the bottom temperature increased from 1205°C to 1223°C, which took 4.5 to 5 minutes; The top temperature of the transition section drops from 1204°C to 950°C, and the bottom temperature drops from 1223°C to 950°C, which takes 2 to 2.1 minutes; The top temperature of the quenching section drops from 950°C to 584°C, and the bottom temperature drops from 950°C to 586°C, which takes 2 to 2.5 minutes; The top temperature of the slow cooling section dropped from 584° C. to 97° C., and the bottom temperature dropped from 586° C. to 97° C., which took 11 to 11.6 minutes.

Citation Information

Patent Citations

  • High mullite crystal phase ceramic slurry

    CN106800405A

  • Marble tile blank sintered by using multi-component composite flux at low temperature and preparation method thereof

    CN111892389A

  • Anti-cutting ceramic rock plate and preparation method thereof

    CN112876226A

  • Preparation method of fast-fired ceramic tile and product of fast-fired ceramic tile

    CN113248240A

  • Mullite toughened ceramic rock plate and preparation method and application thereof

    CN113354387A